(untitled) (Theatrum historiae, 2022)
Before the Second Siege of Vienna in 1683, there was a famous tug-of-war between “Easterners” and “Westerners” at Leopold I’s court. At that time, the Habsburg monarchy did not yet boast a “Foreign Office”. The institution in charge of relations with the Ottoman Empire was the Aulic War Council. Its president, Margrave Hermann von Baden, was the leading “Westerner”, and clearly thought that Louis XIV posed a greater menace to the monarchy than the Ottomans did. That is why, when the ambassador extraordinary to Constantinople, Conte Alberto Caprara, started sending alarmist reports in the summer of 1682, Baden manipulated them in a rather breathtaking fashion, almost turning their meaning on its head. The episode poses a fascinating question about the nature of “absolutism”: Was Baden’s “spin doctoring” designed to delude the Emperor himself – or was it part of a complex game enacted with Leopold’s approval?